2017
DOI: 10.1371/journal.pone.0176146
|View full text |Cite|
|
Sign up to set email alerts
|

Social environment during egg laying: Changes in plasma hormones with no consequences for yolk hormones or fecundity in female Japanese quail, Coturnix japonica

Abstract: The social environment can have profound effects on an individual’s physiology and behaviour and on the transfer of resources to the next generation, with potential consequences for fecundity and reproduction. However, few studies investigate all of these aspects at once. The present study housed female Japanese quail (Coturnix japonica) in pairs or groups to examine the effects on hormone concentrations in plasma and yolk and on reproductive performance. Circulating levels of androgens (testosterone and 5-α-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 107 publications
0
17
1
Order By: Relevance
“…This would suggest higher plasma androgen or corticosterone concentrations in group-housed females compared with pair-housed females. However, as we previously found that female Japanese quail housed in pairs had higher circulating androgen levels and tended to have higher circulating corticosterone levels compared with females housed in groups (Langen et al, 2017), we expected that the reverse might also be found.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…This would suggest higher plasma androgen or corticosterone concentrations in group-housed females compared with pair-housed females. However, as we previously found that female Japanese quail housed in pairs had higher circulating androgen levels and tended to have higher circulating corticosterone levels compared with females housed in groups (Langen et al, 2017), we expected that the reverse might also be found.…”
Section: Introductionmentioning
confidence: 78%
“…P0 females were housed in pairs (one female with one male) or in groups (three females with one male), whereas F1 females were housed in pairs (two females, one offspring from each of the P0 treatments) or in groups (four females, two offspring from each of the P0 treatments). All experiments and testing described for P0 generation females (Langen et al 2017), and for F1 generation females from hatching to the beginning of the experimental social conditions (Langen et al 2018) have been published previously. The birds were placed in the experimental social conditions at the age of 29 days in the P0 generation (see Langen et al, 2017) and 24 days in the F1 generation ( Fig.…”
Section: Social Environmentsmentioning
confidence: 99%
See 3 more Smart Citations